Indonesian and English Cultural Values in Buku Bahasa Inggris Textbook Grade 8 - Qamarina, Dian; Arianti, Theresia (Foremost Journal, 2023)
Textbooks play an important role in introducing students to various cultures. Majority of English teachers only concentrate on teaching four language skills rather than introducing culture to their students. It is critical to analyze cultural aspects in textbooks, particularly in English subjects, to ensure that the cultural values are represented in the English textbook. This study was conducted to find out multicultural values of the source culture and target culture that are represented in Buku Interaktif Bahasa Inggris, discover what techniques of multicultural values of the source culture and target culture are represented, and find out what culture is more represented in Buku Interaktif Bahasa Inggris. This study used content analysis method in order to collect and analyze the data. The result of this study shows that source culture is strongly represented in the textbooks, with National Geography as the multicultural value that mostly appears in the book, conveyed by Geographical Factors as the technique. This study could be useful for both teachers and authors as an input and evaluation so that cultural content can be included and considered in the textbooks or learning process.